In Other Languages: Toward a Critical Pedagogy of Visual Discourse - Patricia Holland Webb (Adult Education Research Conference, 2008)
The language of visuality, despite its ubiquitous “voice” in contemporary global life, is all but ignored in education theory. This paper proposes a theoretical framework for critical pedagogic study of visual meaning structures and interpretation, drawing on psychoanalytic theory, critical theory, and notions of multiliteracy.
Keywords: critical pedagogy; visual discourse; literacy